Spectrophotometric Determination of Gallium(III) as Bipyridylglyoxal bis(4-Phenyl-3-thiosemicarbazone) Derivative - ARAIN, G.M.; DEVI, INDRA; KHUHAWAR, M.Y. (Asian Journal of Chemistry, 2010)
A new simple spectrophotometric method is developed for the determination of gallium. The reagent bipyridyl glyoxal bis(4-phenyl-3-thiosemicarbazone) reacts with Hg(II), V(V), Ru(IV), Ga(III), In(II), and Pt(II) to develop colour in aqueous N,N-dimethylformamide media with maximum absorbance within pH range 2-5. The composition of the metal chelates was examined by variation of the metal: ligand mole ratio. The molar absorptivity was observed within 1.8 × 10-3 to 4.6 × 10-4 L mol-1 cm-1 within 390-448 nm. The linear calibration curves were observed with 0.2 to 20 μg/mL. Highest molar absorpitivity was indicated by gallium(III) with detection limit 0.022 μg mL-1. The proposed method was successfully applied for the determination of gallium(III) from semiconductor and medicinal drug.